Trace Amine-Associated Receptor 1 Agonist Modulates Mismatch Negativity-Like Responses in Mice - Aleksandrov, Aleksander A.; Knyazeva, Veronika M.; Volnova, Anna B.; Dmitrieva, Elena S.; Polyakova, Nadezhda V.; Gainetdinov, Raul R. (Frontiers in Pharmacology, 2019)
The trace amine-associated receptor 1 (TAAR1) is a G protein-coupled receptor widely expressed in the mammalian brain, particularly in limbic system and monoaminergic areas. It has proven to be an important modulator of dopaminergic, serotoninergic and glutamatergic neurotransmission and is considered to be a potential useful target for the pharmacotherapy of neuropsychiatric disorders, including schizophrenia. One of the promising schizophrenia endophenotypes is a deficit in neurocognitive abilities manifested as mismatch negativity (MMN) deficit. This study examines the effect of TAAR1 partial agonist RO5263397 on the MMN-like response in freely moving C57BL/6 mice. Event-related potentials (ERPs) were recorded from awake mice in the oddball paradigm before and after RO5263397 administration. The RO5263397 (but not saline) administration increased the N40 amplitude in response to deviant stimuli. That provided the MMN-like difference at the 36-44 ms interval after the injection. The pitch deviance-elicited changes before the injection and in the control paradigm were established for the Р68 component. After TAAR1 agonist administration the P68 amplitude in response both to standard and deviant stimuli was increased. These results suggest that the MMN-like response in mice may be modulated through TAAR1-dependent processes (possibly acting through the direct or indirect NMDA modulation), indicating the TAAR1 agonists potential antipsychotic and pro-cognitive activity.